Earning Per Share Pada Perusahaan Bursa Efek Indonesia - Rifqy Adli Fadillah; Bakti Setyadi (I-Finance Journal, 2022)
This study aims to determine the effect of ROA, ROE, NPM, DAR and DER either partially or simultaneously on EPS at the Indonesia Stock Exchange LQ45 Issuer Company for the 2017-2021 period. The population in this study is all 45 companies IDX Issuer LQ45 companies. The sample used is as much as 225 data that comes from 5 years multiplied by 45 companies. The data analysis technique used multiple linear regression with hypothesis testing F and t. The results showed that simultaneously ROA, ROE, NPM, DAR and DER both simultaneously affect EPS. Partially, the ROA, ROE, NPM, and DER variables have an effect on EPS while the DAR variable has no effect on EPS.